2023
DOI: 10.3389/fneur.2023.1192644
|View full text |Cite
|
Sign up to set email alerts
|

High level of agreement in a fixed vs. live cell-based assay for antibodies to myelin oligodendrocyte glycoprotein in a real-world clinical laboratory setting

Abstract: IntroductionAs recognition of myelin oligodendrocyte glycoprotein (MOG) antibody-associated disease becomes more widespread, the importance of appropriately ordering and interpreting diagnostic testing for this antibody increases. Several assays are commercially available for MOG testing, and based on a few small studies with very few discrepant results, some have suggested that live cell-based assays (CBA) are superior to fixed CBA for clinical MOG antibody testing. We aimed to determine the real-world agreem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…The majority of our patients with low MOG IgG titres on FCBA had high (clear positive) titres on corresponding LCBA results. This has been emphasised in a recent study that found a high level of agreement between assays, but while titres were comparable, they were not identical ( 13 ). Testing at higher serum dilutions, as recommended in the international criteria, did not contribute additionally to the diagnosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The majority of our patients with low MOG IgG titres on FCBA had high (clear positive) titres on corresponding LCBA results. This has been emphasised in a recent study that found a high level of agreement between assays, but while titres were comparable, they were not identical ( 13 ). Testing at higher serum dilutions, as recommended in the international criteria, did not contribute additionally to the diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…In these studies, both live and fixed CBAs done at multiple centres were compared, using a limited number of samples from patients with either a pre-defined MOG IgG status or a known MOGAD phenotype (10,12). A recent study that compared assay performances in 322 patient samples found an excellent agreement between LCBA and FCBA for the diagnosis of MOGAD (13). The newly developed international MOGAD panel proposed diagnostic criteria that not only emphasised the clinical phenotypes associated with MOGAD but also laid down criteria for interpretation of CBA (both LCBA and FCBA) for definitive diagnosis (14).…”
Section: Introductionmentioning
confidence: 99%
“…Following this operational change, assurance that anti-MOG titers by fixed CBA represent an improvement in the quality of anti-MOG testing we offer is essential to confirm clinical utility of titers we are now reporting as part of routine laboratory practice, and justify their burden on laboratory cost and workflow ( 11 ). This is particularly important for our laboratory because the recommendation by the 2023 MOGAD criteria to perform anti-MOG titers is primarily based on studies of titers using live CBA, which are not identical to titers using fixed CBA ( 8 , 9 , 12 , 13 ). With respect to how to best evaluate the clinical utility of fixed CBA anti-MOG titers, determinations of sensitivity and specificity are limited by the lack of an independent diagnostic gold standard to effectively discriminate between true-negative and false-negative anti-MOG results ( 5 ).…”
Section: Introductionmentioning
confidence: 99%